Characterisation of an antibody specific for coagulation factor VIII that enhances factor VIII activity - Takeyama, Masahiro; Nogami, Keiji; Matsumoto, Tomoko; Soeda, Tetsuhiro; Suzuki, Tsukasa; Hattori, Kunihiro; Shima, Midori (Thrombosis and Haemostasis, 2010)
Many reports have identified factor (F)VIII inhibitory antibodies with epitopes located in all subunits of the FVIII molecule. Antibodies that promote FVIII activity do not appear to have been reported. We characterised, for the first time, a unique anti-FVIII monoclonal antibody, mAb216, that enhanced FVIII coagulant activity. The mAb216 shortened the activated partial thromboplastin time and specifically increased FVIII activity by ~1.5-fold dose-dependently. FXa generation and thrombin generation were similarly increased by ~1.4- and ~2.5-fold, respectively. An A2 epitope, not overlapping the common A2 epitope, was identified and the antibody was shown to enhance thrombin (and FXa)-catalysed activation of FVIII by modestly accelerating cleavage at Arg372. The presence of mAb216 mediated an ~1.5-fold decrease in Km for the FVIII-thrombin interaction. Enhanced FVIII activity was evident to an equal degree, even the presence of anti-FVIII neutralising antibodies with epitopes in each subunit. In addition, mAb216 depressed the rates of heat-denatured loss of FVIII activity and FVIIIa decay by 2 to ~2.5-fold. We have developed an anti-A2, FVIII mAb216 that augmented procoagulant activity. This enhancing effect could be attributed to an increase in thrombin-induced activation of FVIII, mediated by cleavage at Arg372 and a tighter interaction of thrombin with the A2 domain. The findings may cast new light on new principles for improving the treatment of haemophilia A patients.
Keywords: A2 epitope; enhancing antibody; FVIII activation; stability; thrombin